The Analysis of Fishing Effort by Gill Net in Tanah Merah Village Rangsang Pesisir Subdistric Meranti Regency of Riau Province - Maskinah '; Hendrik '; M. Ramli (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
Research on analysis fishing effort by gill net was condsuded on februari 2015 in tanah merah village, rangsang pesisir subdistrict, kepulauan meranri, regency of riau province. This research aims to analyse large capital investment and business expenses issued, profits and big business with the feasibility of using tools jaring kurau gill net. By method by survey with the determination respondents sampling method purposively namely fisherman instrument a gill net with the size of a fleet of the number of respondents as many as 6 people fishermab consisting of 3 fishing boad owners 5 and 3 gt fishing boad.The average investment of gill net jaring kurau on ship 5 gt is Rp.297.110.000 and the average gill net investment 6 gt is Rp.339.550.000 the fishing effort 5 gt time of the season in one raid is Rp.2.575.000 and time is Rp.1.814.000 season. And in one year the average of profit is Rp.43.875.000.Keywords: gill net, worthiness of business investment, rangsang pesisir.